Acute major gastrointestinal bleeding caused by hookworm infection in a patient on warfarin therapy: A case report. Issue 11 (March 2018) - Meng, Yu; Lu, FangGen; Shi, Lin; Cheng, MeiChu; Zhang, Jie
Abstract: Rationale: The use of anticoagulants is a contributor to gastrointestinal (GI) bleeding. Most bleeding patients on anticoagulant therapy such as warfarin commonly have basic lesions existing in their GI mucosa. Patient concerns: We report a case of major GI bleeding following the use of anticoagulants in a patient with hookworm infection. Diagnoses: The patient was diagnosed with nephrotic syndrome with pulmonary embolism. Interventions: He was treated with anticoagulants and suffered from acute major GI bleeding during the treatment. Capsule endoscopy revealed many hookworms in the lumen of jejunum where fresh blood was seen coming from the mucosa. Outcomes: The patient was successfully rescued and cured with albendazole. Lessons: Latent hookworm infection can be a cause of massive small-bowel hemorrhage in patients on anticoagulant therapy and anthelmintic treatment is the key to stop bleeding.